2011
DOI: 10.1016/j.ssc.2010.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental study of Fe/Cr nanometric quasiperiodic multilayers

Abstract: a b s t r a c tAn experimental and theoretical study of magnetization curves of Fe/Cr nanometric magnetic films grown with the structure of the quasiperiodic Fibonacci sequence is presented. Fe ferromagnetic films with interfilm exchange coupling provided by intervening Cr non-ferromagnetic layers were grown on MgO (100) by dc magnetron sputtering at 300• C. The magnetization curves were investigated using the magneto-optical Kerr effect with the external field applied along the easy axis. The theoretical appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A year later, Merlin et al 6 reported performing the first quasiperiodic superlattice following the Fibonacci sequence. More recently, first quasiperiodic Fe/Cr magnetic multilayers with biquadratic coupling were grown experimentally 7 , illustrating the development of crystal growth techniques, which allow substantial thickness control for each layer.…”
Section: Introductionmentioning
confidence: 99%
“…A year later, Merlin et al 6 reported performing the first quasiperiodic superlattice following the Fibonacci sequence. More recently, first quasiperiodic Fe/Cr magnetic multilayers with biquadratic coupling were grown experimentally 7 , illustrating the development of crystal growth techniques, which allow substantial thickness control for each layer.…”
Section: Introductionmentioning
confidence: 99%
“…From an experimental perspective, advances in experimental growth techniques have enabled the synthesis of high‐quality magnetic multilayers grown in different crystallographic orientations through either sputtering or molecular beam epitaxy (MBE) . Quasiperiodic Fe/Cr multilayers presenting biquadratic and bilinear couplings have been experimentally synthesized, thereby exemplifying these technical improvements (). The magnetic properties of these materials strongly depend on the stacking pattern of the layers, which can now be arranged in an unusual fashion if necessary.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, layered magnetic systems have became promising for technological applications, particularly as magnetic sensors and memories of random access [8]. As a matter of fact, very recently, Fibonacci quasiperiodic Fe/Cr multilayers were grown on MgO (100) using dc magnetron sputtering [9].…”
Section: Introductionmentioning
confidence: 99%